1997
DOI: 10.1038/sj.bjp.0701229
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of two serine residues of wild type and constitutively active β2‐adrenoceptors to the interaction with β2‐selective agonists

Abstract: 1 We have studied the di erence in receptor binding activity between partial and full b 2 -adrenoceptor agonists and the abilities of the agonists to interact with Ser 204 and Ser 207 in the ®fth transmembrane region of the b 2 -adrenoceptor, amino acid residues that are important for activation of the b 2 -adrenoceptor. (7)-isoprenaline) and b 2 -(83% and 74% of (7)-isoprenaline) adrenoceptors. 4 The a nities of full agonists, TA-2005 and (7)-isoprenaline, were markedly decreased by substitution of Ala for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…37,38 Through ligand-binding measurements for a number of -receptor chimeras and site-directed mutants, Kikkawa et al have determined that a single residue, Y308 in the extracellular end of TM7 in the 2 -receptor, is responsible for -receptor subtype selectivity for TA-2005. 39 This residue is a phenylalanine in 1 and 3 -receptors.…”
Section: Resultsmentioning
confidence: 98%
“…37,38 Through ligand-binding measurements for a number of -receptor chimeras and site-directed mutants, Kikkawa et al have determined that a single residue, Y308 in the extracellular end of TM7 in the 2 -receptor, is responsible for -receptor subtype selectivity for TA-2005. 39 This residue is a phenylalanine in 1 and 3 -receptors.…”
Section: Resultsmentioning
confidence: 98%
“…This suggested that the 8-hydroxycarbostyril nucleus in conjunction with the side chain geminal methyls and phenyl group are contributing factors to the slow dissociation and low K i of 11a. It has been proposed that the hydroxyl and amido groups of 8-hydroxycarbostyril correspond to the pand m-hydroxyl groups of catecholamines, respectively, and may interact with the same serine residues in the β 2 AR (Yoshizaki et al 1976;Kikkawa et al 1997). Interestingly, replacement of the 8-hydroxycarbostyril of 11a with catechol (14) reduces the affinity of the latter by 48-fold.…”
Section: Discussionmentioning
confidence: 99%
“…The transfection procedure, membrane preparation, receptor binding assays, and cyclic AMP accumulation assays were performed as described previously (Kikkawa et al ., 1997b).…”
Section: Methodsmentioning
confidence: 99%